REPOSITIONING THE VICTIM’S LEGAL STANDING: TRANSFORMING UNLAWFUL ACT LAWSUITS INTO SUBSTANTIVE RESTITUTION EXECUTION CERTAINTY IN ASSAULT CASES UNDER LAW NO. 20 OF 2025." - Stefanus Fernandus Pardosi; Faizin Sulistio; Djumikasih (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study examines the paradigm shift in criminal procedure law, moving from an offender-centered focus toward the restoration of victim rights through restitution mechanisms. Article 101 of the old Criminal Procedure is considered to have failed in providing effective justice because it positioned compensation as an "accessory" claim subject to civil procedure. This placed the burden of independent proof on the victim and resulted in court orders that were difficult to execute. Using normative legal research with a conceptual approach, this study analyzes the urgency of Law No. 20 of 2025 (the New Criminal Procedure Code), effective as of January 2, 2026. The results indicate that Articles 183-192 of the New Criminal Procedure Code carry out a significant transformation by fully integrating restitution into the criminal justice system. This innovation shifts the burden of proof to the Public Prosecutor and provides enforcement power through substitute imprisonment for offenders who refuse to pay. This procedural transformation cuts through the complexity of judicial bureaucracy and guarantees legal certainty and substantive recovery of victim rights. This arrangement serves as a solution to the legal vacuum and the ineffectiveness of the old mechanism, particularly in ordinary criminal cases, to realize comprehensive restorative justice.